PERMIAN CORALS FROM CHITRAL (NW PAKISTAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
The present paper describes the species Pseudobuangia chitralica,  Yatsengia hangchowensis, ? Protomichelinia multitabulata multitabulata,  Protomichelinia guizhouensis flexuosa, Protomichelinia siyangensis and Sinopora ? cf. syrinx  from the Baroghil region of NW Pakistan. The fauna originates from different levels, from the Sakmarian to the Artinskian, or even a more younger.
Keywords: Corals; Taxonomy; Permian; Pakistan.